Japan at war : - Cook, Haruko Taya (The New Press, 1992)
Approximately three million Japanese died in a conflict that raged for years over much of the globe, from Hawaii to India, Alaska to Australia, causing death and suffering to untold millions in China, southeast Asia and the Pacific Islands, as well as pain and anguish to families of soldiers and civilians around the world. Yet how much do we know of Japan's war?In a sweeping panorama, Haruko Taya and Theodore Cook take us from the Japanese attacks on China in the 1930s to the Japanese home front during the devastating raids on Tokyo, Hiroshima and Nagasaki, offering the first glimpses of how this violent conflict affected the lives of ordinary Japanese people.'Oral History of a compellingly high order.' Kirkus Reviews'This book seeks out the true feelings of the wartime generation [and] illuminates the contradictions between official views of the war and living testimony.'